Left atrial appendage closure for stroke prevention in nonvalvular atrial fibrillation: A current overview. Issue 5 (May 2023) - Ueno, Hiroshi; Imamura, Teruhiko; Tanaka, Shuhei; Fukuda, Nobuyuki; Kinugawa, Koichiro
Abstract: Atrial fibrillation (AF) is the most common arrhythmia encountered in clinical practice and its prevalence increases with age. AF causes palpitations, heart failure, and cardiogenic embolism. Of them, the most critical and fatal complication is a cardio-embolic event. Oral anticoagulation plays a central role in reducing stroke risk in AF patients. Recently, when oral anticoagulation is considered in patients with non-valvular AF who are eligible for direct oral coagulations, they are preferred to vitamin K antagonist based on accumulating evidence. Although many patients can tolerate oral anticoagulation, there is a subset of patients who cannot tolerate long-term oral anticoagulation. Such a subset has a higher bleeding risk as indicated by the HAS-BLED score under oral anticoagulation. This subset of patients requires effective and safe non-pharmacological alternative therapies for stroke prevention. One of the promising non-pharmacological therapies is left atrial appendage closure. Three randomized controlled trials demonstrated non-inferiority of percutaneous left atrial appendage closure using WATCHMAN family to oral anticoagulation (Boston Scientific, Marlborough, MA, USA). WATCHMAN FLX, which was innovated following WATCHMAN 2.5, was associated with fewer safety events and a higher success rate of effective appendage closure. Nevertheless, several unsolved issues remain, including device-related thrombosis, post-treatment antithrombotic therapy, and peri-device leakage. Left atrial appendage closure for patients with non-valvular AF may be an alternative therapy to avoid cardiac embolism for high bleeding risk patients with contraindications to long-term oral anticoagulation therapy. Graphical abstract: Unlabelled Image Highlights: Atrial fibrillation (AF) causes cardiogenic embolism which is the critical complication. Oral anticoagulation (OAC) plays a central role in reducing stroke risk in AF patients. There is a subset of patients who cannot tolerate OAC due to high-bleeding risk. One of the promising non-pharmacological therapies is left atrial appendage closure (LAAC). LAAC may be an alternative therapy to avoid stroke for AF patients with high bleeding risk by OAC.